Evaluation of the Effectiveness of the H.A.N.D.S.SM Program: A School Nurse Diabetes Management Education Program. (December 2015) - Breneman, Charity B.; Heidari, Khosrow; Butler, Sarah; Porter, Ryan R.; Wang, Xuewen
The purpose of this project was to determine the effectiveness of the Helping Administer to the Needs of the Student with Diabetes in Schools (H.A.N.D.S. sm ) continuing education program in improving the level of experience and competence in performing services associated with diabetes care. This program is a live course for school nurses providing clinical information about diabetes management and their professional role in the care of students with diabetes. Pre- and post-surveys were administered via e-mail to assess their level of experience and competence in diabetes care. A total of 105 nurses completed both surveys and were included in the analysis. The changes between pre- and post-survey questions were assessed. The H.A.N.D.S. participants' levels of experience and competence for each of the four categories of diabetes care improved significantly, and a greater number of nurses reported being able to perform the services independently and having the ability to teach others.